2005
DOI: 10.1186/1471-2261-5-30
|View full text |Cite
|
Sign up to set email alerts
|

JTT-130, a microsomal triglyceride transfer protein (MTP) inhibitor lowers plasma triglycerides and LDL cholesterol concentrations without increasing hepatic triglycerides in guinea pigs

Abstract: BackgroundMicrosomal transfer protein inhibitors (MTPi) have the potential to be used as a drug to lower plasma lipids, mainly plasma triglycerides (TG). However, studies with animal models have indicated that MTPi treatment results in the accumulation of hepatic TG. The purpose of this study was to evaluate whether JTT-130, a unique MTPi, targeted to the intestine, would effectively reduce plasma lipids without inducing a fatty liver.MethodsMale guinea pigs (n = 10 per group) were used for this experiment. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
41
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 80 publications
(42 citation statements)
references
References 30 publications
1
41
0
Order By: Relevance
“…Intestinal MTP has become a hot topic since new inhibitors of intestinal MTP have been shown to lower triglyceride without causing hepatic steatosis at least in animal studies [84,85]. Although many polymorphisms of MTP have been described, some of which have considerable impact on LDL cholesterol in both non-diabetic and diabetic subjects [86,87], it is difficult to know whether the results mainly stemmed from the effect in the liver rather than the intestine.…”
Section: Microsomal Triglyceride Transfer Proteinmentioning
confidence: 99%
“…Intestinal MTP has become a hot topic since new inhibitors of intestinal MTP have been shown to lower triglyceride without causing hepatic steatosis at least in animal studies [84,85]. Although many polymorphisms of MTP have been described, some of which have considerable impact on LDL cholesterol in both non-diabetic and diabetic subjects [86,87], it is difficult to know whether the results mainly stemmed from the effect in the liver rather than the intestine.…”
Section: Microsomal Triglyceride Transfer Proteinmentioning
confidence: 99%
“…Further, significant atherogenic inflammation with an increase in aortic cytokines has been documented in guinea pigs. The mechanisms of certain drugs affecting triglyceride metabolism can also be explored (Aggarwal et al, 2005;Aggarwal et al, 2006). However, no advanced atherosclerotic lesions have been observed in guinea pigs (Lynch et al, 1996;Singh et al, 2009), and the literature considering guinea pigs as surrogates to surgical models is quite sparse.…”
Section: Guinea Pigsmentioning
confidence: 99%
“…Patients must be kept on a low lipid diet to limit severe diarrhoea symptoms, while in clinical trials liver damage accompanied by liver steatosis was observed (29). Other compounds of this class currently being tested specifically target MTP in the intestines to avoid hepatotoxicity (30,31). Mipomersen is an ASO drug inhibiting the synthesis of ApoB-100, a major constituent of LDL particles, at the mRNA level (32).…”
Section: Presentmentioning
confidence: 99%